Uterine Necrosis Associated with Fusobacterium necrophorum Infection - T. Widelock; R. Elkattah; S. Gibbs; Z. Mashak; S. Mohling; S. DePasquale (Case Reports in Obstetrics and Gynecology)
Fusobacterium necrophorum is infrequently implicated as a pathogenic organism. When pathogenic, the typical clinical presentation is that of pharyngitis, cervical adenopathy, and unilateral thrombophlebitis of the internal jugular vein. Infections caused by Fusobacterium necrophorum within the fields of obstetrics and gynecology have been infrequently reported. We describe a 19-year-old woman who underwent a cesarean delivery complicated by sepsis and purulent uterine necrosis secondary to Fusobacterium necrophorum infection.